Pengembangan Aplikasi Berbasis Android Mahir Baca Kitab (AARAVI) untuk Membangun Daya Saing Internasional Mahasiswa Pendidikan Agama Islam UIN Maulana Malik Ibrahim Malang - Furdianto, Muafan; Mustofa, Bisri; Fitrotulloh, M. Rofik (STAI Ihyaul Ulum Gresik, 2021)
PAI teachers have an important role to participate in building and directing Indonesian Islam As academics of Islamic sciences, book reading skills are an inseparable part of PAI students. Unfortunately, the level of student ability is still weak. This is very unfortunate, considering that they are conditioned as scholars in the Islamic field but cannot study their field of knowledge through access to primary resources in ArabicTherefore, an android-based application development program was initiated called Proficient in Reading Books (AARAVI) for Islamic Studies students which is an alternative to facilitate the process of learning to read books. This learning media development research is based on Multimedia-based Instructional Design using the ADDIE model. The ADDIE model goes through 5 stages of research, namely: (1) Analysis (analysis); (2) Design (design); (3) Development (development); (4) Implementation (application); (5) Evaluation (evaluation).The subjects of this study were students majoring in Islamic Religious Education at UIN Maulana Malik Ibrahim Malang batch of 2020 who were taking the Qira'atul Polar course as many as 20 people. In this AARAVI application development research, data were collected through five data sources, namely: (1) interviews, (2) literature study, (3) questionnaires, (4) tests, and (5) documentation. In this development research, three techniques were used. data analysis, namely: (1) descriptive analysis (2) quantitative descriptive analysis, this is used to process the data obtained through a questionnaire in the form of percentages. (3) as well as the analysis technique of the paired sample t-test (if the data is normally distributed) and the Wilcoxon rank tests (if the data is not normally distributed) to measure the pre and post tests. The results of this application development research indicate that the AARAVI application is very feasible to be applied as a learning medium for reading books for PAI students. This is based on the results of the validation test of material experts in the field of study with a cumulative value of 43 out of 12 statements with a percentage of 89% which means very valid, by media experts getting a cumulative score of 40 out of 12 questions with a percentage of 83% which means very valid and by students majoring in Islamic Studies. UIN Maulana Malik Ibrahim Malang as a field test is 42 of 12 statements with a percentage of 87%. which means it is very valid. There is a positive and significant difference between student learning outcomes before and after the trial. This means that learning by using the product developed is effective in order to increase student learning acquisition in reading skills, so that the product is suitable for use for Islamic Education students at the mubtadi'in level